Penyuluhan Kesehatan Tentang “Kenali, Cegah Dan Kendalikan Penyakit Hipertensi” Di Posyandu Puskesmas Air Putih Samarinda - Barolym Tri Pamungkas; Miftakhul Nadiah; Siti Maulani Jabal Rahma; Ayu Nashari Azmi (STIKES Columbia Asia Medan, 2025)
Patient compliance with hypertension treatment is an important factor, as hypertension is a disease that cannot be cured but must always be controlled to prevent complications that could lead to death. The aim of this health promotion is to increase public understanding of the signs, prevention, and control of hypertension. The activity methodology uses a one-group pre-post design by measuring knowledge before and after the counseling session. The instrument used was a knowledge questionnaire related to the signs, prevention, and control of hypertension. The results achieved after conducting the counseling titled